Policy measures and instruments used in European countries to increase biosimilar uptake: a systematic review - Machado, Sara; Cruz, Agostinho; Ferreira, Pedro Lopes; Morais, Carminda; Pimenta, Rui Esteves (Frontiers in Public Health, 2024)
Introduction: While biosimilar medicines can contribute to the sustainability of healthcare systems, their utilization rate varies across European countries. This study aims to identify and systematize policy measures and instruments used in European countries to increase biosimilar market share.Methods: A systematic review was conducted according to PRISMA 2020 recommendations. Medline-PubMed, Web of Science and ScienceDirect databases were searched using inclusion criteria that required full articles published in English between January 2006 and November 2023. Reviews, letters, reports, editorials and comments or opinion articles were excluded from this study.Results: Of the 1137 articles, only 13 met the eligibility criteria for analysis, which covered a total of 28 European countries. Pricing regulation measures were found in 27 of these countries with tendering, price-linkage and internal reference price being the most used. Tendering was used by 27 countries to procure biosimilars in inpatient setting. Prescribing guidelines and recommendations were the widely used instrument. Some European countries adopted physician incentives, quotas, and prescription by international non-proprietary name.Automatic substitution was not commonly recommended or applied. Interchangeability and switching will become increasingly relevant issues. It is important that the positive results from some countries serve as an example for the future of these medicines in the European market.